The acute effects of oral administration of phytic acid-chitosan-magnetic iron oxide nanoparticles in mice - Mohd Tamsir, Norain; Mohd Esa, Norhaizan; Shafie, Nurul Husna; Hussein, Mohd Zobir; Hamzah, Hazilawati; Abdullah, Maizaton Atmadini (MDPI, 2019)
A nanocomposite, phytic acid-chitosan-magnetic iron oxide nanoparticles (IP6-CS-MNPs) has been used to treat colon cancer in vitro, previously. However, its potential toxicity in vivo has yet to be elucidated. Hence, the present study aimed to evaluate the acute effects of oral administration of IP6-CS-MNPs in mice. In this study, 1000 and 2000 mg/kg body weight (b.w) of IP6-CS-MNPs were orally administered to two different groups of BALB/c mice, once. Additionally, the mice in the control group were given only deionized water. After 14 days of post-IP6-CS-MNPs administration, in a similar way to the untreated mice, the treated mice showed no sign of mortality and abnormalities. However, the serum urea level of mice receiving 2000 mg/kg b.w of IP6-CS-MNPs was significantly higher than the control group (p < 0.05). The mice that received 1000 mg/kg IP6-CS-MNPs showed a significantly higher level of serum alkaline phosphatase (ALP) compared to the control group. However, there were no significant histopathological changes seen in the liver and kidneys of treated mice compared to the untreated group.